VD_FINDINFO Jug / 2016 / 272 vom 9. März 2016 - VD Tribunal cantonal (2016)
PRINCIPE DE LA BONNE FOI, ÉGALITÉ DE TRAITEMENT, TITRE UNIVERSITAIRE | 5 al. 3 Cst., 8 al. 1 Cst., 9 Cst., 23 LPers-VD, 24 LPers-VD, 6 RSRC